Effects of polyacrylamide hydrogel used in the treatment of osteoarthritis on mesenchymal stem cells and human osteoblasts - Nasırcılar, Aşkın; Bülbül, Muhammet Volkan; Kalender, Semiha Mervenur; Bozkurt, Celal; Keskin, İlknur (Journal of Surgery and Medicine, 2022)
Background/Aim: Adipose-derived mesenchymal stem cells (AD-MSCs) have gained popularity for use in treating osteoarthritis (OA) although their long-term effects remain unsatisfactory for treating the end stages of OA. However, clinically injectable polyacrylamide hydrogels (PAHGs) remain in the joint indefinitely, which could make them ideal candidates as AD-MSC carriers. Our aim was to evaluate whether combinations of PAHG and AD-MSCs have positive effects on cell viability, thereby the potential of this combination prior to clinical use in OA treatment in addition to the effects of PAHG on human osteoblasts (HOBs). Methods: Cell lines of AD-MSCs of canine origin and HOBs were culture-expanded and seeded in 96-well plates (0.5 x 105 cells/well). The PAHG substrate at doses of 2, 6, 10, 20, or 40 µL per 200 µL of sample were added to the wells, and their effects were compared to the positive and negative control groups and among substrate doses for each cell line. The experiments were repeated three times, and cell viability was studied using tetrazolium (MTT) method. Results: Cell viability in all dose groups was significantly greater than that of their negative control groups for both cell lines (P < 0.001). Among the different dose groups, significant dose-dependent viability increases were only observed for the HOB cell line (P < 0.001). The PAHG substrate was not lethal to AD-MSCs or HOBs up to the maximum assayed doses and had positive effects on the viability of these cell lines, including slight increases in proliferation. Conclusion: Combination of PAHG with AD-MSCs may have positive long-term effects for OA treatment. However, further trials are needed.